Risk assessment for antibiotic resistance in South East Asia. (5th September 2017) - Chereau, Fanny; Opatowski, Lulla; Tourdjman, Mathieu; Vong, Sirenda
Abstract : Fanny Chereau and colleagues assess the risk of the emergence and spread of antibiotic resistance in South East Asia and suggest it is the highest of the World Health Organization regions